Effect of hot pressing and reinforcement of TiC and WC on the mechanical properties and microstructure of AlCuFeCrNi HEAs alloy - Akkaş Mehmet; Al Sudani Fatimah Ridha Abbood (National Library of Serbia, 2021)
In this study, a powder mixture consisting of TiC (titanium carbide) and WC (tungsten carbide) reinforced AlCuNiFeCr was produced using the hot pressing technique. The AlCuNiFeCr powder mixture, TiC and WC were added at a rate of 5 %, 10 % and 15 %, respectively. In order to produce and control to produce parameters have been produced having automation systems type of laboratory a hot pressing machine. Graphite moulds were used in production and sintering processes were carried out in a protective argon gas atmosphere. Composites were produced at a sintering temperature of 900?C and under a pressure 35 MPa and for 4 minutes. To understand the microstructure and mechanical properties of produced specimens, their SEM and EDS analysis, XRD analysis, fracture surface SEM images, SEM mapping of elemental distribution and EDX spectrums, hardness, three-point bending, and corrosion tests were investigated. As a result, the best sample has been identified that belong to AlCuNiFeCr-15 % WC with great features.
Keywords: hot pressing; Chemical technology; wc reinforcement; TP1-1185; high-entropy alloy (hea); mechanical properties; tic reinforcement